Roe and Dobbs in Context : Under the Societal Hood of Abortion in America - Barnett, Larry D. (International Studies in Sociology and Social Anthropology, 2025)
Roe and Dobbs in Context describes long-term demographic changes that underlie Roe v. Wade and Dobbs v. Jackson Women's Health Organization and concludes that, as the Court suggests in Dobbs, Americans accept women's participation in politics and hence in formulating law and government policy. The book examines the state of American public opinion on abortion and its impact on government regulation, investigates whether culture or religion is the source of the morality that underlies U.S. law on abortion and thus whether law-embodied protections of religion apply to government efforts to restrict abortion access. Finally, Larry Barnett reviews and critiques social science studies of the impact of law on the incidence of abortion and considers possible side effects of anti-abortion law along with two historical events (the War on Drugs and Prohibition) that, together with an evident need for access to abortion, indicate there will be a negligible long-term impact on abortion frequency in America from abortion-hostile law.